The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1137/18m1218480
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Filtering of Interpolant Observables for a Discrete-in-Time Downscaling Data Assimilation Algorithm

Abstract: We describe a spectrally-filtered discrete-in-time downscaling data assimilation algorithm and prove, in the context of the two-dimensional Navier-Stokes equations, that this algorithm works for a general class of interpolants, such as those based on local spatial averages as well as point measurements of the velocity. Our algorithm is based on the classical technique of inserting new observational data directly into the dynamical model as it is being evolved over time, rather than nudging, and extends previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Indeed, an advantage of nudging is the flexibility of the interpolant. Practically speaking, Fourier modes are not expected to be directly measured in observed data, but could be obtained via a fast Fourier transform from data at nodes on a grid, albeit with an aliasing error (see [9] for more on spectral filtering of observables). The first algorithm we consider utilizes data collected on all the variables (except the pressure).…”
Section: Remarkmentioning
confidence: 99%
“…Indeed, an advantage of nudging is the flexibility of the interpolant. Practically speaking, Fourier modes are not expected to be directly measured in observed data, but could be obtained via a fast Fourier transform from data at nodes on a grid, albeit with an aliasing error (see [9] for more on spectral filtering of observables). The first algorithm we consider utilizes data collected on all the variables (except the pressure).…”
Section: Remarkmentioning
confidence: 99%
“….. K > 0 here is an integer dependent on N , the minimum length scale λ (see Section 5) and the number of nodes in the probe, m h . For N = 2 12 and ν = 7.5e − 6, the frequency-locked velocities were observed to correspond to the value K = 64. It was found that the probe took significantly longer to converge or it did not converge at all at these velocities.…”
Section: Sweeping Probe Data Assimilationmentioning
confidence: 85%
“…In addition to this, the resulting matrix is tri-diagonal, so solving this system has a time complexity of only O(N ) using the Thomas algorithm. In every simulation in this work, we use time-step ∆t = 1e − 3 for stability, and spatial resolution N = 2 12 = 4096 (i.e., ∆x = 2 −12 ≈ 2.441e − 4), which are sufficient to resolve the spatial scales in our simulations (i.e., below the cubic aliasing cut-off number N/4) to machine precision over the range of ν-values and µ − values we consider. Note that since we handle the data assimilation term explicitly, a CFL condition arises, requiring ∆t ≤ 2/µ, which is satisfied in all of our simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This seemingly minor change had profound impacts, and the authors of [5] were able to prove that using only sparse observations, the CDA algorithm applied to the 2D Navier-Stokes equations converges to the correct solution exponentially fast in time, independent of the choice initial data. This stimulated a large amount of recent research on the CDA algorithm; see, e.g., [3,6,7,10,11,13,17,18,19,20,21,22,27,31,30,35,40,41] and the references therein. The recent paper [15] showed that CDA can be effectively used for weather prediction, showing that it can indeed be a powerful tool on practical large scale problems.…”
mentioning
confidence: 99%